(untitled) (Research, Society and Development, 2021)
Several therapeutic benefits of medicinal plants are attributed to antioxidant properties, since antioxidant compounds play an important role in the prevention of various diseases and aging. Many products have synergistic action from combinations of plant extracts that contain natural antioxidants. The present study aimed to evaluate the synergistic effect of Pfaffia glomerata extract with Arrabidaea chica extract for antioxidant action. In the study the extract of the inflorescences of P. glomerata and the extract of the leaves of A. chica were used. The synergism between P. glomerata extract and A. chica extract was evaluated using the ratio between experimental and theoretical antioxidant activity, which was determined using the DPPH method and the potential total reactive antioxidant method (TRAP). The combination of P. glomerata extract and A. chica extract showed a synergistic effect, in which the antioxidant property of this combination was substantially superior to the sum of the individual antioxidant effects. This demonstrates that the combined extracts can be important for the development of products that have a high antioxidant potential.